การวิจัยและพัฒนาผลิตภัณฑ์น้ำจิ้มสุกี้เพื่อสุขภาพจากกากกระเทียมที่หมักด้วยเชื้อโพรไบโอติก เพื่อส่งเสริมเศรษฐกิจชุมชนเทศบาล ตำบลบ้านถ้ำ อำเภอดอกคำใต้ จังหวัดพะเยา - สุวรรณสม นิจติยา (Area Based Development Research Journal, 2014)
การวิจัยนี้เป็นการวิจัยและพัฒนาโดยใช้กระบวนการวิจัยเชิงทดลองมีวัตถุประสงค์เพื่อศึกษาสภาวะที่เหมาะสมของการหมักกากกระเทียมร่วมกับหัวเชื้อโพรไบโอติกที่ได้จากน้ำกระเทียมดองและสร้างสูตรน้ำจิ้มสุกี้จากกากกระเทียมหมักและถ่ายทอดเทคโนโลยีสู่ชุมชนในพื้นที่เทศบาลตำบลบ้านถ้ำ อำเภอดอกคำใต้ จังหวัดพะเยาผู้ร่วมกระบวนการวิจัย ประกอบด้วย (1) กลุ่มแม่บ้านที่รวมกลุ่มกันเพื่อหารายได้เพิ่มจากอาชีพหลักจำนวน 19 ราย (2) ผู้นำชุมชน ได้แก่ อสม. นักพัฒนาชุมชน หัวหน้าสำนักปลัดเทศบาลและนายกเทศบาลตำบลบ้านถ้ำ จำนวน 6 ราย การเก็บรวบรวมข้อมูลและเครื่องมือวิจัย ประกอบด้วย การสำรวจพื้นที่ การสัมภาษณ์ การประชุมกลุ่มการอบรมเชิงปฏิบัติการ การทดลองผลิตน้ำจิ้มสุกี้จากกากกระเทียมหมัก การวิเคราะห์คุณภาพผลิตภัณฑ์ แบบสอบถามความพึงพอใจ การทดสอบการยอมรับของผู้บริโภควิเคราะห์สังเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา ผลการวิจัยพบว่า สภาวะที่เหมาะสมในการหมักกากกระเทียมคือใช้หัวเชื้อน้ำกระเทียมดองที่มีความเข้มข้นของเชื้อโพรไบโอติก 106 CFU/ml หมักทิ้งไว้ที่อุณหภูมิห้องเป็นระยะเวลา 7 วันเป็นต้นไป จะให้ปริมาณกรดแลคติกมากที่สุด มีการเจริญของเชื้อโพรไบโอติกได้สูงสุดและไม่พบการปนเปื้อนของเชื้อก่อโรค ซึ่งสามารถนำกากกระเทียมหมักไปผลิตน้ำจิ้มสุกี้ โดยมีการนำผลิตภัณฑ์ที่ได้ไปทดสอบทางประสาทสัมผัส ได้แก่ สี กลิ่น รสชาติ ลักษณะเนื้อสัมผัส และทดสอบการยอมรับของผู้บริโภคต่อผลิตภัณฑ์โดยรวม ผลการศึกษาการยอมรับของผู้บริโภคต่อผลิตภัณฑ์น้ำจิ้มสุกี้ พบว่า น้ำจิ้มสูตรกวางตุ้งได้รับคะแนนความชอบสูงกว่าน้ำจิ้มสูตรไหหลำ และการศึกษาการเก็บรักษาผลิตภัณฑ์น้ำจิ้มสุกี้ที่อุณหภูมิห้องเป็นเวลา 12 สัปดาห์ พบว่า มีคุณภาพทางกายภาพ คือ ค่าความเป็นกรด-ด่าง (pH) และปริมาณจุลินทรีย์ ปริมาณยีสต์และราไม่เกินค่ามาตรฐานของมาตรฐานผลิตภัณฑ์ชุมชนและประกาศกระทรวงสาธารณสุข การถ่ายทอดเทคโนโลยีทำให้กลุ่มแม่บ้านสามารถรวมกลุ่มกันและนำองค์ความรู้ที่ได้ไปผลิตผลิตภัณฑ์น้ำจิ้มสุกี้จากกากกระเทียมที่หมักด้วยเชื้อโพรไบโอติกที่มีคุณภาพเพื่อวางจำหน่ายภายในชุมชนเทศบาลเอง โดยมีการใช้วัตถุดิบในท้องถิ่นมาใช้เป็นส่วนประกอบด้วย มีการออกแบบตราสัญลักษณ์และฉลากที่แสดงเอกลักษณ์ของชุมชนรวมทั้งทำแผ่นพับประชาสัมพันธ์ข้อมูลเกี่ยวกับผลิตภัณฑ์และข้อมูลด้านสุขภาพเกี่ยวกับโพรไบโอติก นับเป็นการส่งเสริมรายได้ชุมชนและใช้วัตถุดิบอย่างคุ้มค่าจากกากกระเทียมที่เป็นของเหลือใช้ Development of Health Product and Technology Transfer to Increase Income of Farmers and Housewives in the Communityof Ban Tham Sub-district, Dokkamtai District, Phayao Province : Probiotic Sukiyaki Sauce from Fermented Garlic Waste with Lactic Acid Bacteria The present research aimed to investigate appropriate conditions for a production of Sukiyaki probiotic sauce from a garlic waste. The lactic acid bacteria were used to perform a fermentation process. The garlic waste was obtained from Tambon Ban Tham community, Amphur Dokkamtai, Phayao province. There were 25 people who participated this project, including 19 members of housewife and 6 community leaders, which were health volunteers, head of Municipal Clerk and head of Sub-district Municipality. Data was collected through several strategies including an area-based survey, an interview, a group discussion, workshop training, a lab scale’s Sukiyaki sauce production, a product quality analysis, a questionnaire related to the satisfaction towards the product as well as a consumer test. The data was analyzed using descriptive statistics. It was found that the best conditions for fermentation were required 106 cfu/ml of the lactic acid probiotic to be incubated with the garlic waste at room temperature. The fermentation was carried out for at least 7 days. This condition then led to the highest lactic acid production which subsequently inhibited the growth of other harmful pathogens. This fermented garlic residue was further used to produce Sukiyaki probiotic sauces. A descriptive test for the Sukiyaki sauce in terms of color, aroma, flavor, texture and satisfaction study for the product was performed. Among the two recipes, the Cantonese sauce’s recipe was shown to be more favorite than the Hainan sauce’s recipe. The quality of Cantonese Sukiyaki sauce was further investigated, once kept at room temperature for 12 weeks. The pH test and the total plate count for bacteria, yeast and mold did not exceed safety standard defined by the Thai community Product Standard and the Thai FDA Registration. The successive method for the production of fermented garlic waste and the Sukiyaki probiotic sauce were transferred through the housewife group in Tambon Ban Tham community. High quality Sukiyaki sauce was later produced and sold in the community marketplace. A logo of the product was also designed to express a unity of Tambon Ban Tham. Furthermore, the booklet which was presented the product facts and the positive effect of probiotic to human health was prepared and distributed throughout the community. This project was fulfilled our aim in which the lab-based knowledge was transferred to community. Moreover, it could help the community to set up and run their own business to increase the community incomes as well as has provided a worthy solution to a garlic waste management ever since.